A critical analysis of cross-culture issues in M&A--- The case of DaimlerChrysler Merger: a cultural mismatch? - wu, xue (2009)
Nowadays, mergers and acquisitions are becoming more and more popular method used by firms to strengthen their market share and power. They are regarded as an efficient and relatively fast method to incorporate new technologies and expand into new markets. However, the enterprises involved in the process of cross-border mergers and acquisitions will encounter a wide range of cultural differences and conflicts. To achieve success, the leaders always take in consideration with the influence of these issues during the post-merger integration process, at the same level as the business performance and profit improvement.